2018
DOI: 10.1101/357996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host dietary specialization and neutral assembly shape gut bacterial communities of wild dragonflies

Abstract: 21Host-associated gut microbial communities can have large impacts on host ecology and 22 evolution, and are typically shaped by host taxonomy and diet. Different host species often 23 harbor distinct microbial communities, potentially because (1) host dietary specialization 24 determines microbial colonization, (2) host-specific selection acts on diet-acquired microbiota, 25and (3) a combination of both processes. While the first possibility involves passive 26 community structuring, the other two may arise f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…The present results do not conform to the hypothesis that generalist species should have more diverse gut microbial communities (Deb et al, 2019), as confirmed in scavengers and omnivores (Shukla et al, 2016; Yadav et al, 2015; Yun et al, 2014). The generalist Ceratitis species had lowest gut microbial diversity (around two genus equivalents).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The present results do not conform to the hypothesis that generalist species should have more diverse gut microbial communities (Deb et al, 2019), as confirmed in scavengers and omnivores (Shukla et al, 2016; Yadav et al, 2015; Yun et al, 2014). The generalist Ceratitis species had lowest gut microbial diversity (around two genus equivalents).…”
Section: Discussioncontrasting
confidence: 90%
“…They depend on insect ecology, a major feature of which is host range, that is, the host plant species an insect uses. For instance, one could expect that insect species specialized on different host plants encounter different initial microbe pools and that generalist insect species encounter a more diverse set of microbes than specialist species (Deb et al, 2019). Second, host phylogeny could potentially structure insect gut microbiota through different mechanisms ranging from active filters (constrained by host development, immune function morphology, and physiology), to the sharing of similar microbe pools (through social interactions or similarity in diet; Brooks et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The copy number data were obtained by digital droplet PCR (ddPCR) to allow calculation of the bacteria/ host (B/H) cell ratio [38] for each sample. This approach has also been used to analyse bacterial load in insect samples with low mass and volume [39][40][41], with the use of a ratio accounting for differences in sample size. Primers targeting single-copy reference genes in E. diaphana and A. salina were used for host cell quantification (Table 3).…”
Section: Bacterial Load Assessment (B/h Ratio)mentioning
confidence: 99%
“…Insects represent one of the best-studied animals in this context, with a large number of studies showing that insect-microbiome interactions are shaped by host taxonomy, host diet, and environmental factors [ 5 8 ]. Importantly, insects present a spectrum of host-microbial associations ranging from transient and neutrally assembled microbiomes [ 9 12 ], to established relationships whereby hosts use microbial symbionts to extract dietary nutrients, digest toxins, provide essential metabolic precursors, or protect from pathogens [ 3 , 7 ]. To understand the factors that drive this spectrum of interaction strength, we need model systems where the host-microbiome interaction is suitably poised both for the evolution of a strong mutualism, as well as its breakdown.…”
Section: Introductionmentioning
confidence: 99%